China and the Emerging Global Energy System (Journal of International Studies, 2020)
Energy and resource security have become critical issues on the economic and strategic agenda in the Asian region as demand and dependence on imported supplies grow. Energy security cuts across many sectors–economic, environmental and national security. Recent increases in energy prices, climate change and a steady escalation in global energy demand –expected to rise by nearly 60% over the next 20 years–have led energy policy-makers across the world to engage in a wide ranging debate over how best to address their country’s future energy requirements. Regional powers, most notably China, have responded with nationalistic strategies to secure control over energy and commodity supplies. China is trying to shift its role from a passive recipient to an active innovator of international energy rules; from an onlooker to an active participant in international energy affairs; and from a receiver to a contributor of international energy policy. Major Asian powers are now redefining their foreign policy to meet the growing energy needs. This is most evident from the grand strategy adopted by China since 1991. China is destined to become a significant player in key energy- and resource-exporting regions, such as the Middle East, Central Asia, Africa, and Latin America. China’s new involvement in these regions could have a powerful impact on the strategic goals of other major power in the world. Asian stability is central to the global prosperity and security; thus, the potential for conflict driven by energy competition and resource insecurity must become a conscious and carefully crafted dimension of energy strategies of all leading players in the region.